The Impact of Deep Learning Approach on Student`s Cognitive Abilities in Penerokan - Arifannisa; Tri Putri Wahyuni (Gateway for Understanding Research in Education, 2026)
Traditional teacher-centered instruction often hinders the development of critical thinking, leading to poor cognitive outcomes. At SD 48/1 Penerokan, only 8 of 28 students achieved learning mastery. The purpose of the study was to determine the influence of deep learning learning on the cognitive improvement of students in elementary school. Using a quasi-experimental post-test only control group design, the study compared an experimental class using deep learning with a control group. Results showed the experimental group averaged 74.80, significantly higher than the control group's 67.20. A t-test confirmed a significant difference (0.037 < 0.05). Thus, the deep learning approach effectively enhances students' cognitive abilities.